Nutrition perspective from the view of pregnant women: their understanding of fetal well-being relative to their diet: NUTRITION PERSPECTIVE FROM THE VIEW OF PREGNANT WOMEN - Aynaci, Gülden (Progress in Nutrition, 2019)
Introduction: Nutritionally balanced nutrition assessment, mothers' nutrition motivation, and healthy nutrition information are among the factors that affect infants. Thus, it is possible to shed light on the attempts to reach information in healthy nutrition guides among pregnant women. Aim: The aim of our study was to evaluate the nutritional habits and healthy nutrition knowledge levels of pregnant women. It was aimed to evaluate whether pregnant women should be included in high quality nutrition programs. Methods: Our study was performed with volunteer 338 pregnant women who presented to Trakya University obstetrics clinic in March 2018- April 2019. Sociodemographic characteristics were recorded. The General Knowledge Nutrition Questionnaire (GNKQ) was used in our study. Results: The differences in GKNQ scores for the pregnant women in our study were evaluated for the four sections and total scores. For the first section, dietary recommendations, the mean was score was 9.66. For the second section (sources of nutrients), the mean score was 32.92. For the third section (choosing everyday foods), the mean sore was 6.23, and for the fourth section (diet-disease relationships), the mean score was 10.24. The mean total score was 59.10. It was seen that most of the pregnant women had not received adequate nutrition education before or during pregnancy. It was observed that some of the pregnant women participated in our study because of the threat of preterm labor and / or premature membrane rupture. 3.84% were found to have preterm history. When evaluated with the GNKQ scale, those with a history of EMR were under investigation and treatment due to the threat of preterm labor. In our study, it was seen that patients who were interned in the ward because of gestational hypertension, preeclampsia, and eclampsia GNKQ scores were lower than in the other patients. This result suggests that nutrition may have an effect on the complications of pregnancy. Unfortunately, although women reported positive changes in lifestyles during pregnancy, it was shown that their dietary intake and knowledge did not meet the recommended nutrient intake for pregnancy. Discussion: Considering that diet behavior is very complex, attempts to understand this in terms of nutritional knowledge in pregnant women should start with a clear understanding of awareness. Furthermore, they had a wide range of information, but the correct information was not on a systematic basis. Pregnancy is a life event that triggers a long-term review of nutritional problems. It is important for health professionals to realize that pregnancy is one of the unique opportunities for women to be informed about nutrition. There is a need for greater emphasis on nutritional counseling and education in order to optimize the quality of nutritional habits of pregnant women. Training and forms should be put into practical use for pregnant women. Conclusion: Our findings show that evaluating pregnant women with the GNKQ and providing nutritional education will be beneficial on pregnancy outcomes. This study showed that pregnant women had limited knowledge about balanced nutrition rules. It’s necessary to increase effective nutrition programs and campaigns for pregnant women. Babies should be provided with a healthy start to life and routine nutrition counseling should be promoted as part of pregnancy care.